Antimicrobial susceptibility of Streptococcus pneumoniae, Haemophilus influenzae and Moraxella catarrhalis isolated from community-acquired respiratory tract infections in China: Results from the CARTIPS Antimicrobial Surveillance Program. (June 2016) - Zhang, Yawei; Zhang, Feifei; Wang, Hui; Zhao, Chunjiang; Wang, Zhanwei; Cao, Bin; Du, Yan; Feng, Xianju; Hu, Yunjian; Hu, Bijie; Ji, Ping; Liu, Zhiyong; et al.
Highlights: First report on susceptibility profiles of major CARTI pathogens in China, 2013–2014. Rates of PNSSP varied from different cities, with the highest rate in Nanchang. Fluoroquinolones had good activity against S. pneumoniae, H. influenzae and M. catarrhalis . The susceptibility to macrolides and β-lactams among these pathogens were decreasing. Abstract: This study investigated the antimicrobial susceptibilities of Streptococcus pneumoniae, Haemophilus influenzae and Moraxella catarrhalis isolates causing adult community-acquired respiratory tract infections (CARTIs) in China. A multicentre resistance surveillance study (CARTIPS) investigating 1046 clinical isolates from 19 hospitals in China was conducted from 2013 to 2014. Based on the minimum inhibitory concentration (MIC) breakpoints of oral penicillin, the percentages of penicillin-resistant, penicillin-intermediate and penicillin-susceptible S. pneumoniae were 44.1%, 13.7%, and 42.2%, respectively. The rates of penicillin-non-susceptible S. pneumoniae ranged from 27.9% to 72.2% in different cities, with the highest rate in Nanchang. Macrolides, including azithromycin, clarithromycin and erythromycin, showed the lowest activities against S. pneumoniae isolates, with resistance rates of 90.5%, 92.2% and 93.0%, respectively. However, 98% of these strains were susceptible to levofloxacin and moxifloxacin. For H. influenzae isolates, most of the antimicrobials agents exhibited good activities. However, ampicillin and trimethoprim/sulfamethoxazole showed relatively lower activity against H. influenzae, with resistance rates of 35.0% and 54.4%, respectively. β-lactamase production rates amongst H. influenzae and M. catarrhalis were 31.0% and 87.1%, respectively. In addition, a total of 15 β-lactamase-negative ampicillin-resistant (BLNAR) strains identified in this study were resistant to ampicillin, amoxicillin/clavulanic acid, cefaclor and cefuroxime. Most of the antimicrobial agents showed excellent activity against M. catarrhalis, with susceptibility rates of >90%. The results from the current study confirmed the regional variations in antimicrobial susceptibility of major CARTI pathogens and provided some choices for the treatment of these organisms. Continuous national surveillance of the epidemiology of CARTIs is strongly warranted in China.